Optimization of agricultural production under climate change up to 2050 in Pelagonia region - Buzarovska, Daniela (SLU/Dept. of Economics, 2012)
This study aims to illustrate the variation in crop area in Pelagonia region in 2050 due to increased irrigation requirements of crops. The allocation of the crop area depends on the net return per unit of crop area. On the other side, the net return is strongly related to the irrigation water requirements. Both, rain-fed and irrigated crops are expected to have higher water demand driven by the higher temperatures and reduced soil moisture because of the decreased precipitation and runoffs. This study uses three climate scenarios for 2050. The optimistic scenario (2050 Low) where predicted climate variations are mild and the outcome is more optimistic, the most realistic scenario (2050 Medium) with the most expected outcome and pessimistic scenario (2050 High) with the highest variations in temperature and precipitation and the most negative outcome. The future climate change scenarios are subject to comparison with the Base case scenario that is a plausible interpretation of the today’s climate conditions. The technique of linear optimization is used to identify the best cropping pattern under given constraints. The proposed methodology is applied to assess the economic value of the crop production in Pelagonia region given the climate change. The study examines alternative crop production pattern in Pelagonia region which is one of the most important agricultural region in the Republic of Macedonia. The study is underpinned only by the climate variations in the forthcoming period, using assumptions and features such as constant ratio between price and costs in 2050, as in 2010. Other socio-economic factors including price movements based on future supply and demand, investments in agricultural productivity, technology and infrastructure, as well as other production factors are not taken into consideration in this study. The findings of the study show that due to climate divergences in 2050, the crop structure differs in various climate scenarios. In general, the more severe climate in 2050 will cause decrease in net returns by 11% in the most optimistic scenario (2050 Low) and 22% in the pessimistic scenario (2050High), if no adaptation measures are applied. The production of the low profitable crops (cereals, industrial and fodder crops) will be reduced to their minimal levels, while the production of high profitable crops such as vegetable, especially green pepper, tobacco and other crops that increase net return per crop area should be intensified. The strategy of greater specialization in commodities in which Macedonia has a comparative advantage and potential trade with other countries which have comparative advantage in other commodities might prove to be economically efficient and valuable for both countries.